Experimental mechanics of solids and structures - Oyo, Yang (New delhi: Amiga Press, 2021)
Experimental Mechanics of Solids and Structures also replaces mechanical testing in a larger context: firstly, that of the experimental model, with its own hypotheses. The mechanics are a physical science, since it deals with the study of physical phenomena. However, some associate mechanics with mathematics, while many consider it as an engineering subject. Both these views are justified in part. Mechanics is the foundation of most engineering sciences and is an indispensable prerequisite to their study. The mechanics are the body of knowledge that deals with the relationships between forces and the motion of points through space, including the material space. This book is devoted to the basic variations principles of mechanics. This book presents the classical tools in the experimental approach to mechanical engineering.
Includes Bibliography and index
Keywords: Experimental Mechanics of Solids -- Solids and Structures -- Crystal Classes; Physics Experiment in Solid, Liquids and Gases -- Principles of Mechanics